Pengaruh Edukasi Investasi, Persepsi Risiko Dan Kemajuan Teknologi Terhadap Mahasiswa Dalam Minat Investasi Saham - Rio Susanto; Nugraeni Nugraeni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Investment is a commitment of a number of funds or other resources carried out at this time, with the aim of obtaining a number of benefits in the future. According to Sukirno, investment activities carried out by the community will continuously increase economic activities and employment opportunities, increase national income, and improve the level of public welfare. Investment interest is the desire to know about investments ranging from types, advantages, disadvantages, investment performance and so on. This study was conducted to determine the influence of investment education, risk perception and technological advances on student interest in stock investment. Researchers used the slovin formula to determine the number of samples used in the study, with a sample number of 62 respondents. The research method uses multiple linear regression, classical assumption test, validity test, reliability test and t test. The results showed that investment education, risk perception and technological advances did not affect students' interest in investing in stocks.